BORROWING A WORD AS A SOCIOLINGUISTIC FACTOR CONTRIBUTING TO INTERLANGUAGE CONTACT (Scientific journal of the Fergana State University, 2024)
The article analyzes the influence of sociolinguistic, extralinguistic, intralinguistic, psychological, social and pragmatic factors on the occurrence of language contact.